(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Marking of metal products is essential in many industrial processes. It is mandatory for the finished products according to regulations of the European and world legislation. Traditional marking usually creates contrasting symbols that can easily be erased and forged.In recent years, a new method for product identification has appeared - color marking. One of the advantages of this method is that it is difficult to counterfeit. This article aims to present the progress of color marking technology on two types of materials. Three groups of factors have been analyzed: the laser source; the technological process; material properties. Their role in obtaining a specific color marking on Ti and AISI 304 is shown. The results are presented in tables. Each color can be repeated only with strict observance of the three groups of factors.